Cognitive and affective reflection increases appreciation for less preferred subcategories of experiential goods - Crolic, Cammy; Janiszewski, Chris (Frontiers in Psychology, 2023)
Attitudes, particularly negative attitudes toward experiential goods, are difficult to change. As a result, people tend to choose and consume experiential goods from their preferred subcategory (e.g., prefer impressionist art so primarily choose to view impressionist paintings) while disregarding options from less preferred subcategories (e.g., ignore cubist or surrealist paintings). This research investigates the consequences of reflection while consuming experiential goods from less preferred subcategories. Namely, an initial, negative reflexive response can be overridden by a reflective appraisal which increases appreciation for experiential goods from less preferred subcategories. Six studies show how a reflective appraisal differs from a reflexive response (i.e., a reflective appraisal has more cognitive and affective thoughts than evaluative thoughts, respectively), that reflective appraisals can supplant reflexive responses to experiential goods in less preferred subcategories, and that reflective appreciation training encourages reflective appraisal. A reflective appraisal improves the intent to consume, enhances appreciation of the consumption, and increases the consumption of novel experiential goods in less preferred subcategories.